Assessment of Lung Function using Spirometry and Radiological findings in Post Tuberculosis Cases - Shahzeb Ahmad Satti; Abdul Moueed Tariq; Abdul Latif Khattak; Salman Saleem; Rafi ud Din; Azhar Ali Chaudhry (Life and Science, 2020)
Objective: To assess the prevalence of abnormal radiological changes and their impact on lung function in post tuberculosis cases. Study Design: Descriptive cross-sectional study. Place and Duration of Study: The study was conducted in medical Outpatient Department (OPD) of CMH, Quetta from 30th Nov 2018 to 30th May 2019. Materials and Methods: A total of sixty treated cases of pulmonary tuberculosis, presenting in medical OPD of CMH Quetta for regular follow-up, were included in the study. The subjects were recruited by non-probability consecutive sampling technique according to predefined inclusion criteria. Demographic data including age, gender, post treatment duration, clinical features and history of asthma, atopy, rhinitis, biomass exposure, coalmine exposure, animal and pet exposure was collected. Their lung function was assessed using spirometry and radiological changes were assessed by either chest X-ray or high resolution CT chest. Results: Among the 60 patients, mean age was 36.32 + 9.95 years. The majority (70%) of subjects were males (n=42).The mean duration post treatment was 4.79 + 4.25 years. Among the study population 51.7% (n=31) were symptomatic, 73.3% (n=44) had abnormal lung function tests. With those having abnormal lung functions tests, 23.3% (n=14) had obstructive, 43.3% (n=26) had restrictive and 6.7% (n=4) had mixed airway disease. The radiological investigations were abnormal in 80% (n=48) of the patients showing various radiological changes such as reticular shadows, nodules, pleural thickening, collapse, fibrotic bands, hilar calcifications, lung volume reduction and traction bronchiectasis. Conclusion: Our study showed that the restrictive pattern was most common finding on spirometry while, fibrotic bands were the most common radiological findings in post tuberculosis cases in our population.